ANALISIS KOMPARATIF PENGGUNAAN SISTEM PEMBAYARAN BEA BALIK NAMA (BBN) LAMA DAN BARU TERHADAP EFISIENSI KAS PT ABC - Erna Dwi Setyawati; Indrawati Yuhertiana (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
Payment of Transfer Fee (BBN) is the main requirement in the process of issuing Vehicle Registration Certificate (STNK) and Motor Vehicle Ownership Book (BPKB) in the name of the new owner. Without payment of BBN, the transfer process cannot be completed and the STNK and BPKB cannot be issued in the name of the legitimate owner. PT ABC is a company engaged in the sale of new cars, spare parts, and after-sales services. In its operational activities, the company uses an internal system called AMS as a business process control tool. Over time, the AMS system has undergone updates that significantly affect the efficiency of BBN payments. This system update has had a significant impact, reflected in an average increase of more than 80% in the number of BBN payments successfully processed compared to the previous system. This study uses secondary data. The method used is secondary data observation.